Betydningen af Keynes metodologi for aktuel makroøkonomisk forskning - en Ph.D. forelæsning - Finn Olesen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2007)
– In the history of economic thought many Post Keynesian scholars of-fer a distinct interpretation of John Maynard Keyness General Theory. One of the fundamentals of Post Keynesianism in this regard is the statement that the way Keynes understood economics can not be understood correctly if one does not take the methodology of Keynes into account. And Keynes could rightfully be said to have started a methodological as well as a theoretical revolution in economics. In the present paper the content of the methodology of Keynes is highlighted followed by a discussion to what extent this methodology could be said to have influenced modern macroeconomics. Most weight in this respect is given to a presentation of some core elements of the Keynes-like tradition of Post Keynesianism. Jeg skal takke Jesper Jespersen for værdifulde kommentarer til den oprindelige version af dette papir. En tidligere version af nærværende artikel dannede baggrund for min Ph.D. fo-relæsning, der fandt sted den 8. marts 2007 på Roskilde Universitetscenter.
Keywords: 330